Pengaplikasian Standar ISO 9126 di Aplikasi Layanan Instalasi Software Perkuliahan Mahasiswa Berbasis Android - Alkodri, Ari Amir; Fitriyani, F; Isnanto, Burham (LPPM STIKOM Tunas Bangsa, 2024)
The student lecture software installation service is an essential facility that supports the smooth running of lectures by helping students install the necessary software on their personal laptops. Although this service is crucial, the manual process is often inefficient and poorly documented. This study aims to design an Android application to enhance the quality of the student lecture software installation service, focusing on effectiveness, efficiency, and user satisfaction. The research methods included interviews and questionnaires with students, lab assistants, and laboratory staff, followed by prototype application development and testing using ISO 9126 standards. The main findings show that the developed application meets ISO 9126 standards in terms of usability, efficiency, functionality, and reliability. This success indicates that the application can provide a fast, accurate, and up-to-date solution for presenting software installation service information via smartphone devices for each lab assistant or laboratory staff. The unique contribution of this study is the integration of mobile technology into the software installation service process, which was previously conducted manually, thereby improving efficiency and process documentation. In conclusion, this application not only meets the needs of students but also enhances the operational effectiveness of laboratories, with positive implications for the future development of technology-based educational services.